Digital Image Processing and Digital Holography in Optical Diagnostics of Plasmas - Watkins-Orellana, F; Castro-Barrera, M; Pedreros, J (OSA - The Optical Society, 2016)
The potentiality of the digital holography technique applied to transparent objects is discussed in terms of the set of refractive optical diagnostics (Interferometry, Shadowgraphy and Schlieren technique), which can be reconstructed with a single interferometric record. © OSA 2016.